Determining Factors of Audit Delay With Audit Quality as a Moderating Variable - Mahira, Nabila Khansa; Wahyuni, Sri; Haryanto, Eko; Azizah, Siti Nur (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2024)
Audit delay is a critical aspect in the realm of financial auditing, reflecting the time lapse between the end of a financial reporting period and the completion of the audit. This delay can be influenced by various factors. Understanding these determinants is crucial for improving the effectiveness and timeliness of audit processes. This research aims to analyze the influence of Profitability, Liquidity and Leverage on Audit Delay using Audit Quality as a moderating variable. This research is quantitative research. The sampling technique was purposive sampling and the sample size was 78 company data. The data used is secondary data. Data collection was carried out using documentary data. The analysis techniques in this research are the classic assumption test, F test, determination test, and T test using the SPSS application. The research results show that 1) Profitability has no effect on Audit Delay, 2) Liquidity has no effect on Audit Delay, 3) Leverage has a significant negative effect on Audit Delay, 4) Audit Quality is able to moderate the influence of liquidity and leverage on Audit Delay.